A COMPARITIVE STUDY ON THE CELLULAR VIABILITY AND APOPTOSIS POTENTIAL OF PALMYRA SAP SAMPLE COLLECTED FROM KANYAKUMARI AND TIRUNELVELI DISTRICTS - Dr. T.SHERIN MARY (The Bioscan, 2025)
Borassus flabellifer Linn., of the Arecaceae family is locally called as Tal, English Name: Palmyra palm.Traditional cuisines have been employed the fruit pulp of Borassus flabellifer L. and the sap that was collected from the flower section as a sweetener for diabetes patients. Proteins, lipids, carotenoid, vitamin B complex, ascorbic acid and other minerals are found in the Palmyra apart from sugars. Besides all Palmyra fruits are also rich in immunosuppressive effects. Palmyra sap itself is generally not described as cytotoxic in research, but rather is known for its nutritional and various health-promoting properties, including antioxidant, anti-inflammatory, and hepatoprotective effects. Extracts from this part contain compounds that exhibit potent cytotoxic effects against certain cancer cells. In the present research, the cytotoxic effect of Palmyra sap collected from Kanyakumari and Tirunelveli Districts against normal cell lines were studied and the results reported significant increase in the cytotoxic effect in the increasing concentration of the sample. The sap exhibited minimal cytotoxic effects on Normal L929 cells across various concentrations, with a dose-dependent effect noted. The overall results indicate that even if both samples have less toxic effect on normal cell lines, the Palmyra palm sap samples collected from Tirunelveli district showed higher toxic effect with less viability than the samples collected from Kanyakumari district. The cytotoxic effects were more pronounced at higher concentrations, indicating potential for selective use in anticancer applications.